1977
DOI: 10.1042/bj1630385
|View full text |Cite
|
Sign up to set email alerts
|

The role of the imidazolyl nitrogen atoms of histidine-12 in ribonuclease S

Abstract: S-peptide (residues 1--14) analogues in which the active histidine-12 residue is replaced by Npi-methyl-L-histidine, Ntau-methyl-L-histidine and beta-(pyrid-3-yl)-L-alanine were synthesized and tested for their capacity to bind to S-protein and to activate it. The results show that both imidazolyl nitrogen atoms are required for optimal catalytic functioning, Ntau being essential to the catalytic reaction itself, Npi playing a role in keeping the imidazole ring in the correct position.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1979
1979
2006
2006

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…of the imidazole moiety of histidine in the active site of many enzymes (Fersht, 1985;Walsh, 1979), histidinyl residues of peptide ligands have also been shown to influence binding to protein receptors. In a series of thorough experiments it was shown that the His residue of the S-peptide (residues 1-20) of ribonuclease A influenced both binding of S-peptide to S-protein (residues 21-124) and the activity of the resulting peptide-protein complex (Dunn et al, 1974;Van Batenburg et al, 1977).…”
Section: Discussionmentioning
confidence: 99%
“…of the imidazole moiety of histidine in the active site of many enzymes (Fersht, 1985;Walsh, 1979), histidinyl residues of peptide ligands have also been shown to influence binding to protein receptors. In a series of thorough experiments it was shown that the His residue of the S-peptide (residues 1-20) of ribonuclease A influenced both binding of S-peptide to S-protein (residues 21-124) and the activity of the resulting peptide-protein complex (Dunn et al, 1974;Van Batenburg et al, 1977).…”
Section: Discussionmentioning
confidence: 99%
“…A growing interest has recently been focused on the synthesis of unnatural α-amino acids; their use in the fields of peptide and combinatorial chemistry as conformational constraints, molecular scaffolds, and chiral auxiliaries is related to the development of new leads in peptidic and nonpeptidic compounds . The class of nonproteinogenic heterocyclic α-amino acids is of particular interest in this context due to their diverse range of chemical and biomedicinal applications not only as components of peptides and peptide nucleic acids (PNAs) but also as free amino acids (e.g. the antitumor−antibiotic agent l -azatyrosine 4a ).…”
Section: Introductionmentioning
confidence: 99%
“…When combined together in a non-covalent complex, the two peptide segments combine to form an enzyme with 100% activity. This type of peptide or fragment complementation system was the first system in which "mutants" of the wild type enzyme could be tested in an in vitro assay system, as it allowed for a number of amino acids to be substituted for in the wild type enzyme by direct replacement of the amino acid via peptide synthesis (24). A number of other examples of peptide complementation are known in the literature including S. aureus nuclease, soybean trypsin inhibitor, and thioredoxin (25)(26)(27).…”
mentioning
confidence: 99%